Study of magnitude of anaemic problem in rural tertiary care centre in outpatient department - V., Anjaneya Prasad; C., Anjani Kumar; V., Neelima; R., Sai Prasanth (International Journal of Research in Medical Sciences, 2018)
Background: Prevalence of anaemia is very high in rural tertiary care hospital O.P.D patients. Anemia is the most common morbidity among micronutrients and affects health, education, economy, and productivity of the entire nation. Anemia, like fever, is a manifestation and not a disease per se. The most common group among the causes for anemia is malnutrition and among that group, iron deficiency makes up the bulk of it. Girls are more likely to be a victim due to various reasons. In a family with limited resources, the female child is more likely to be neglected. She is deprived of good food and education and is utilized as an extra working hand to carry out the household chores. The added burden of menstrual blood loss, normal or abnormal, precipitates the crises too often. Anemia can usually be prevented at a low cost, and the benefit/cost ratio of implementing preventive programs is recognized as one of the highest in the realm of public health. This information has equipped everyone in public health to take action against this long-standing problem and to do whatever is needed to be done. Methods: In our study 200 people attending medical outpatient department at a tertiary care centre were enrolled. Assessment of the anaemic problem is worked out. Results: Out of 200 patients, 107 were females and 93 were males. 49 females out of 107 had haemoglobin less than 10 and 9 males out of 93 are having haemoglobin less than 10. Among people with hemoglobin less than 10, 84.5% are females. Significant p value was observed in females (<0.0001). Conclusions:Anemia continues to be a major health problem in developing countries like India, particularly rural India. Despite different strategies and programs have been taken by government of India the growing menace of anaemia is not solved. So newer strategies must be taken. Background: Prevalence of anaemia is very high in rural tertiary care hospital O.P.D patients. Anemia is the most common morbidity among micronutrients and affects health, education, economy, and productivity of the entire nation. Anemia, like fever, is a manifestation and not a disease per se. The most common group among the causes for anemia is malnutrition and among that group, iron deficiency makes up the bulk of it. Girls are more likely to be a victim due to various reasons. In a family with limited resources, the female child is more likely to be neglected. She is deprived of good food and education and is utilized as an extra working hand to carry out the household chores. The added burden of menstrual blood loss, normal or abnormal, precipitates the crises too often. Anemia can usually be prevented at a low cost, and the benefit/cost ratio of implementing preventive programs is recognized as one of the highest in the realm of public health. This information has equipped everyone in public health to take action against this long-standing problem and to do whatever is needed to be done. Methods: In our study 200 people attending medical outpatient department at a tertiary care centre were enrolled. Assessment of the anaemic problem is worked out. Results: Out of 200 patients, 107 were females and 93 were males. 49 females out of 107 had haemoglobin less than 10 and 9 males out of 93 are having haemoglobin less than 10. Among people with hemoglobin less than 10, 84.5% are females. Significant p value was observed in females (<0.0001). Conclusions: Anemia continues to be a major health problem in developing countries like India, particularly rural India. Despite different strategies and programs have been taken by government of India the growing menace of anaemia is not solved. So newer strategies must be taken.